Thermally Induced Activation Energy of Crystalline Silicon in Alkaline Solution - Lamichhane, SK (Nepal Journal of Science and Technology, 2011)
Etching of crystalline silicon by potassium hydroxide (KOH) etchant with temperature variation has been studied. Results presented here are temperature dependent ER (etch rate) along the crystallographic orientations. Etching and activation energy are found to be consistently favorable with the thermal agitation for a given crystal plane. Study demonstrates that the contribution of microscopic activation energy effectively controls the etching process. Such a strong anisotropy in ER on KOH allows us a precious control of lateral dimensions of the silicon microstructure as well as surface growth of the crystal during micro device fabrication. Key words: anisotropy; activation energy; etch rate; lattice parameter; micromachining DOI: 10.3126/njst.v11i0.4148 Nepal Journal of Science and Technology 11 (2010) 215-222